Mechanistic and therapeutic insights into the function of NLRP3 inflammasome in sterile arthritis - Xiao, Yi; Zhang, Li (Frontiers in Immunology, 2023)
The NLRP3 inflammasome, which belongs to the pyrin domain containing 3 family of NOD-like receptors, has a significant impact on both the innate and adaptive immune responses. Regulating host immune function and protecting against microbial invasion and cell damage, the NLRP3 inflammasome plays a crucial role. By triggering caspase-1, it facilitates the development of the inflammatory cytokines IL-1β and IL-18, and triggers cell pyroptosis, resulting in cell lysis and demise. Common sterile arthritis includes osteoarthritis (OA), rheumatoid arthritis (RA) and gouty arthritis (GA), all of which manifest as bone destruction and synovial inflammation in a complex inflammatory state, placing a significant medical burden on the families of patients and government agencies. In the past few years, there has been a growing interest in investigating the impact of cell pyroptosis on arthritis development, particularly the widespread occurrence of pyroptosis mediated by the NLRP3 inflammasome. The NLRP3 inflammasome's biological properties are briefly described in this review, along with the presentation of the fundamental processes of pyroptosis resulting from its activation. Furthermore, we provide a summary of the advancements made in studying the NLRP3 inflammasome in various forms of arthritis and enumerate the intervention approaches that target the NLRP3mediated pyroptosis, either directly or indirectly. These discoveries lay the groundwork for future investigations on medications for arthritis, offering fresh approaches for the clinical identification and treatment of this condition.